The impact of splinting timepoint of mobile mandibular incisors on the outcome of periodontal treatment: preliminary observations from a randomized clinical trial - Sonnenschein, Sarah K.; Ciardo, Antonio; Kilian, Samuel; Ziegler, Philipp; Rütters, Maurice; Spindler, Marcia; Kim, Ti-Sun (Clinical oral investigations, 2022)
Objectives  To compare the outcome of periodontal parameters in mobile mandibular incisors which were splinted before or after full-mouth disinfection (FMD). Materials and methods  Thirty-four periodontitis patients with ≥ 1 mobile mandibular incisor (mobility degree II/III, clinical attachment loss (CAL) ≥ 5 mm, relative bone loss ≥ 50%) were randomly allocated to group A or B. Patients received periodontal treatment (PT) including splinting of teeth 33-43 before (A) or after FMD (B). Patient (age/sex/smoking status/ systemic diseases/number of teeth) and tooth-related parameters (mean probing pocket depth (PPD)/CAL/oral hygiene indices; for the overall dentition and region 33-43) were assessed prior to PT and 12 months after FMD by a blinded examiner. Therapy-related information was added (group/antibiotic therapy/surgical intervention). - Results  Twenty-six patients (A: 12; B:14) were re-examined. Two patients of group B did not need splinting after FMD because of reduction in mobility after FMD. Regression analysis revealed a positive association of antibiotic therapy with CAL_overall, PPD_overall, and PPD_33-43 (p ≤ 0.01). There is a trend toward a higher reduction of periodontal parameters at teeth 33-43 in group A (PPD_33-43: − 0.91 vs. − 0.27 mm; CAL_33-43: − 1.02 vs. − 0.47 mm). - Conclusions  Teeth splinted before or after FMD show a significant improvement in periodontal parameters 12 months after FMD. Splinting after FMD offered the option to detect reduction in mobility. Clinical relevance  Despite a higher, but not statistically significant, improvement in periodontal parameters on teeth splinted before FMD, the results do not indicate which timepoint of splinting is more beneficial. The decision for the therapeutic procedure should therefore be made individually.